1998
DOI: 10.1063/1.121517
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of lateral epitaxial overgrown GaN layers

Abstract: The optical properties of homoepitaxial GaN layers deposited by organometallic vapor phase epitaxy on stripe-patterned GaN films on 6H-SiC substrates have been investigated. Analysis of the spatiallyresolved Raman scattering spectra indicate an improvement in material quality of the overgrown region. Room-temperature color cathodoluminescence imaging and low-temperature photoluminescence measurements indicate that a donor and an acceptor, different from those detected in the underlying GaN/AlN/SiC substrate, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 8 publications
3
26
0
Order By: Relevance
“…A large lattice mismatch between these films and the silicon substrate results in the formation of high dislocation densities and ultimately reduces the emission lifetime and reliability of the device. 5,6 CuCl has a cubic zinc-blende structure with a lattice constant, a CuCl = 5.41 Å, 7 which is close ͑mismatch Ͻ0.4%͒ to that of Si ͑a Si = 5.43 Å, diamond cubic͒. 8 This close match in the crystal system and lattice parameters of CuCl and Si opens up the possibility of realizing Si based UV photonic devices using CuCl as UV emitting layer with low defect density.…”
Section: Introductionmentioning
confidence: 99%
“…A large lattice mismatch between these films and the silicon substrate results in the formation of high dislocation densities and ultimately reduces the emission lifetime and reliability of the device. 5,6 CuCl has a cubic zinc-blende structure with a lattice constant, a CuCl = 5.41 Å, 7 which is close ͑mismatch Ͻ0.4%͒ to that of Si ͑a Si = 5.43 Å, diamond cubic͒. 8 This close match in the crystal system and lattice parameters of CuCl and Si opens up the possibility of realizing Si based UV photonic devices using CuCl as UV emitting layer with low defect density.…”
Section: Introductionmentioning
confidence: 99%
“…Although a detailed study of the optical properties is necessary to clarify the issue, the difference between the two sets of samples is most likely related to the residual strain in the LEO stripes, that is, samples B, C, and D are under slightly larger compressive stress than sample A. 8,9,10 The possibility that the incorporation of impurities depend on the stripe morphology cannot be excluded and could also explain some of the differences between the two sets of samples. Figure 2 illustrates the effect of varying the TMG and NH 3 flow rates over a wide range of conditions while exposing only the {11 2 0} facets, which brings additional insight into the mechanisms of lateral growth.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have confirmed that the density of threading dislocations (TDs) is reduced by 3-4 orders of magnitude in the LEO material grown on 6H-SiC 1 , Al 2 O 3 2,3,4 , and Si(111) 5 substrates, and the mechanisms of threading dislocations evolution with respect to the facet configuration of the LEO stripes have been investigated. 1,4,6,7 Optical studies of LEO GaN 8,9,10 and InGaN quantum wells 9 have been reported. Finally, the use of LEO GaN has resulted in marked improvements in the lifetime of laser diodes, 11 while GaN p-n junctions, 12 InGaN single 13 and multiple 14 quantum well light emitting diodes, and GaN/AlGaN heterojunction field-effect transistors 15 fabricated on LEO GaN exhibit a ~3 orders of magnitude reduction of the leakage current compared to identical devices based on bulk GaN.…”
Section: Introductionmentioning
confidence: 99%
“…This CL characteristic has been observed in polar GaN LEO stripes. [16][17][18] The mottled area extends across the entire width of the [0001 ] stripe, which corresponds to the TEM observation of dislocation bending into the laterally overgrown regions for this stripe orientation. Even though the [0001 ] stripe shown in Fig.…”
Section: R3 A-plane Gan Lateral Overgrowth By Mocvdmentioning
confidence: 99%